2009
DOI: 10.1080/08977190903024298
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neurotrophin 3 in spinal neuroplasticity in rats subjected to cord transection

Abstract: That neuroplasticity occurs in mammalian spinal cord is well known, though the underlying mechanism still awaits elucidation. This study evaluated the role of endogenous Neurotrophin-3 (NT-3) in the spinal neuroplasticity. Following cord transection at the junction between T9 and T10, the hindlimb locomotor functions of rats showed gradual but significant improvement from 7 to 28 days post-operation. Corresponding to this was a significant increase in the level of NT-3 in the cord segments caudal to injury sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Spontaneous locomotor functional recovery was observed after spinal cord injury [1,8,9]. In the present study, proteomics analysis revealed differentially expressed protein spots in the gastrocnemius muscle between spinal cord transection (SCT) and normal rats.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Spontaneous locomotor functional recovery was observed after spinal cord injury [1,8,9]. In the present study, proteomics analysis revealed differentially expressed protein spots in the gastrocnemius muscle between spinal cord transection (SCT) and normal rats.…”
Section: Resultsmentioning
confidence: 90%
“…Monkeys and humans subjected to spinal cord hemisection that transects all corticospinal projections on that side typically exhibit a marked ability to recover volitionally guided locomotion [2][3][4][5][6][7]. Partial functional recovery was also observed in spinal cord transected rats [8,9]. The mechanism underlying the above phenomenon could be associated with spontaneous plasticity in the intraspinal circuitry in some animals [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…However, NGF and BDNF expression recovered at 1 week and surpassed control levels at 2 weeks following differentiation. Other neuroregulatory factors expressed by ADSCs can also regulate neuronal survival and neurogenesis [36,37], and these changes still need to be clarified. We therefore cannot determine whether dADSCs are better than uADSCs for treating neural injuries, as this comparison requires in vitro and in vivo studies to assess therapeutic effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Although BDNF may serve an important role in minimizing neuronal apoptosis during ischemia, it has not been linked to promoting neuroplasticity after ischemia (Oliveira et al 2013). However, it has been demonstrated that neurtrophin-3 (NT-3) promotes axonal migration in damaged spinal cords of mice (Yang et al 2009). Evidence of NT-3 promoting neuroplasticity in the spinal cord suggests that NT-3 is likely the neurotrophin responsible for increased neuroplasticity in the brain after ischemia, however, this has yet to be tested (Kamei et al 2007).…”
Section: Neurotrophins and Neuroplasticitymentioning
confidence: 99%